Spectrophotometric determination of a substance trifusol in a veterinary suppository - Klosova, K. H.; Miedviedieva, K. P.; Vasiuk, S. O.; Bushuieva, I. V.; Кльосова, К. Г.; Мєдвєдєва, Катерина Павлівна; Васюк, Світлана Олександрівна; Бушуєва, Інна Володимирівна; Клёсова, К. Г.; Медведева, К. П.; Васюк, С. А.; Бушуева, И. В. (Запорізький державний медичний університет, 2020)
The purpose of the work was to develop of a method for the quantitative determination of piperidinium 2-[5-(2-furyl)-4-phenyl-1,2,4- triazol-3-ylthio] acetate (trifuzol) as part of a dosage form – an effervescent intrauterine suppository using spectrophotometry in the ultraviolet region spectrum and its validation according to State Pharmacopoeia of Ukraine. Materials and methods. The study was used a working standard sample of trifuzol, intrauterine effervescent veterinary suppositories, 1.0 g of trifuzol, as a solvent – purified water. Analytical equipment: Specord 200 spectrophotometer, electronic scales ABT-120-5DM, ultrasonic bath ELMASONICE 60 H, class A measuring dishes. Method of spectrophotometric analysis was used. Results. A spectrophotometric method has been developed and validated for the quantitative determination of trifuzol in a dosage form – an intrauterine effervescent veterinary suppository, based on measuring the absorption of an aqueous solution of the drug at 278 nm. The methodology tally the requirements of State Pharmacopoeia of Ukraine for such validation characteristics as specificity, linearity, precision, correctness, and robustness. The analysis of the predicted total uncertainty of the analysis was showed the reproducibilityof the method and the possibility of its application in other laboratories. Conclusions. A method for the quantitative determination of trifuzol in the composition of the dosage form, an effervescent intrauterine suppository, according to the requirements of State Pharmacopoeia of Ukraine, was developed and validated. It was proved that according to such validation characteristics as linearity, specificity, precision, correctness, and robustness, the technique is correct

Мета роботи – розроблення методики кількісного визначення піперидиній 2-[5-(2-фурил)-4-феніл-1,2,4-тріазол-3-ілтіо]ацетату (трифузолу) у складі лікарської форми – шипучого внутрішньоматкового супозиторію – з застосуванням спектрофотометрії в ультрафіолетовій області спектра та здійснення її валідації за ДФУ. Матеріали та методи. У дослідженні використали робочий стандартний зразок трифузолу, внутрішньоматкові шипучі ветеринарні супозиторії, 1,0 г трифузолу, як розчинник – воду очищену. Аналітичне обладнання: спектрофотометр Specord 200, ваги електронні АВТ-120-5DM, ультразвукова баня ELMASONICE 60 H, мірний посуд класу А. Застосували метод спектрофотометричного аналізу. Результати. Розроблено та валідовано спектрофотометричну методику кількісного визначення трифузолу в лікарській формі – внутрішньоматковому шипучому ветеринарному супозиторії, – що заснована на вимірюванні абсорбції водного розчину препарату при 278 нм. Методика відповідає вимогам ДФУ за такими валідаційними характеристиками, як специфічність, лінійність, прецизійність, пра¬вильність і робастність. Аналіз прогнозованої повної невизначеності аналізу показав відтворюваність методики та можливість її застосування в інших лабораторіях. Висновки. Розробили та здійснили валідацію методики кількісного визначення трифузолу у складі лікарської форми – шипучого внутрішньоматкового супозиторію – за вимогами ДФУ. Доведено, що за такими валідаційними характеристиками, як лінійність, специфічність, прецизійність, правильність і робастність методика є коректною.

Цель работы – разработка методики количественного определения пиперидиний 2-[5-(2-фурил)-4-фенил-1,2,4-триазол-3-илтио] ацетата (трифузол) в составе лекарственной формы – шипучего внутриматочного суппозитория – с применением спектрофотометрии в ультрафиолетовой области спектра и проведение ее валидации согласно ГФУ. Материалы и методы. В исследовании использованы рабочий стандартный образец трифузола, внутриматочные шипучие ветеринарные суппозитории, 1,0 г трифузола, как растворитель – вода очищенная. Аналитическое оборудование: спектрофотометр Specord 200, весы электронные АВТ-120-5DM, ультразвуковая баня ELMASONICE 60 H, мерная посуда класса А. Применили метод спектрофотометрического анализа. Результаты. Разработана и валидирована спектрофотометрическая методика количественного определения трифузола в лекарственной форме – внутриматочном шипучем ветеринарном суппозитории, – основанная на измерении абсорбции водного раствора препарата при 278 нм. Методика соответствует требованиям ГФУ по таким валидационным характеристикам, как специфичность, линейность, прецизионность, правильность и робастность. Анализ прогнозируемой полной неопределенности анализа показал воспроизводимость методики и возможность ее применения в других лабораториях. Выводы. Разработана и проведена валидация методики количественного определения трифузола в составе лекарственной формы – шипучего внутриматочного суппозитория – согласно требованиям ГФУ. Доказано, что по таким валидационным характеристикам, как линейность, специфичность, прецизионность, правильность и робастность методика корректна.
Спектрофотометричне визначення трифузолу субстанції у ветеринарному супозиторії
Спектрофотометрическое определение трифузола субстанции в ветеринарном суппозитории
Кльосова К. Г.- ORCID ID: 0000-0001-6397-0029; Мєдвєдєва К. П.- ORCID ID: 0000-0001-7260-5728; Васюк С. О.- ORCID ID: 0000-0002-1569-9374; Бушуєва І. В. - ORCID ID: 0000-0002-5336-3900.
Keywords: spectrophotometry; trifuzol; veterinary suppository; quantitative determination; спектрофотометрія; трифузол; ветеринарний супозиторій; кількісне визначення; спектрофотометрия; трифузол; ветеринарный суппозиторий; количественное определение